A Case Study of the Relationship Between Vegetation Coverage and Urban Heat Island in a Coastal City by Applying Digital Twins - Qi, Yansu; Li, Han; Pang, Zonglin; Gao, Weijun; Liu, Chao (Frontiers in Plant Science, 2022)
While Urban vegetation affects the urban thermal environment directly, the effects of different plant layouts and vegetation cover on urban microclimate regulation are different. This study has applied digital technologies to advance urban environmental research and forestry analysis. With a focus on a coastal city located on the eastern coast of the North Temperate Zone as a study area, this paper collected the Landsat archive satellite remote sensing image data covering study area in 2000-2020 and analyzes temporal and spatial distribution characteristics of vegetation coverage, land surface temperature, and urban heat island ratio index. The study resulted in following findings: (1) The area of high fractional vegetation cover (0.8 to 1.0) in the study area is increasing. Those areas are located in the mountain forests in the near-coastal area. The lowest temperature was also detected in the mountain area. (2) The distance from the coastline causes negative correlation between land surface temperature and fractional vegetation cover. The land surface temperature in the regions with a distance of over 25 km from the coastline decreases obviously with increasing fractional vegetation cover in summer. However, the correlation between the land surface temperature and fractional vegetation cover showed a slight change in winter period. (3) Urban heat island ratio index decreases along with the area of high fractional vegetation cover area. The influence of ocean climate on seasons is different, which results in the reduced effect of high fractional vegetation cover area and differences in urban heat island ratio index. (4) The distance from the coastline should be considered as an important factor in forestry development planning of the coastal cities.